2021
DOI: 10.3390/agriculture11070652
|View full text |Cite
|
Sign up to set email alerts
|

The Buzz Changes within Time: Native Apis mellifera mellifera Honeybee Subspecies Less and Less Popular among Polish Beekeepers Since 1980

Abstract: Socio-cultural research might address anthropocentric reasons for honeybee (Apis mellifera) conservation. In some regions, particular honeybee subspecies are considered to be native; A. mellifera mellifera (“dark bee”) in the north-east and A. mellifera carnica in the Island Beskids in Poland. Additionally, A. mellifera caucasia (often incorrectly called A. mellifera caucasica) and Buckfast are reported across Poland. In order to verify the actual choice of beekeepers, a survey on honeybee subspecies kept in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Over 67.1% of the colonies had wing venation patterns more similar to the C-lineage A. m. carnica and A. m. ligustica, to the O-lineage A. m. caucasia, and to the M-lineage A. m. iberiensis than to A. m. mellifera. While A. m. iberiensis could be confounded with A. m. mellifera, detection of the other three subspecies is compatible with the existence of a natural hybrid zone in southern Poland, where the three lineages come together [49], as well as with long-standing importations of foreign queens [34,63]. However, detection of a high proportion of wings assigned with high probability to A. m. ligustica was unexpected, as molecular studies largely reported in Poland the presence of A. m. carnica, but not of the Italian bee [39,58].…”
Section: Discussionmentioning
confidence: 91%
“…Over 67.1% of the colonies had wing venation patterns more similar to the C-lineage A. m. carnica and A. m. ligustica, to the O-lineage A. m. caucasia, and to the M-lineage A. m. iberiensis than to A. m. mellifera. While A. m. iberiensis could be confounded with A. m. mellifera, detection of the other three subspecies is compatible with the existence of a natural hybrid zone in southern Poland, where the three lineages come together [49], as well as with long-standing importations of foreign queens [34,63]. However, detection of a high proportion of wings assigned with high probability to A. m. ligustica was unexpected, as molecular studies largely reported in Poland the presence of A. m. carnica, but not of the Italian bee [39,58].…”
Section: Discussionmentioning
confidence: 91%
“…Espregueira Themudo et al (2020) showed that the genetic diversity of European honey bees had been reduced within a few decades, possibly by selection and breeding for specific traits, and by abandoning the local stock. While it is difficult to obtain reliable estimates of the proportion of beekeepers actively using artificial selection, surveys reporting voluntary replacements and purchase of queens point to high numbers in Europe (Gray et al, 2020;Bieńkowska et al, 2021). Selection and breeding aiming for varroa resistance traits might cause the loss of additional genetic information.…”
Section: Domestication Versus Natural Selection: Impacts On Genetic D...mentioning
confidence: 99%
“…In North America, most honey bees are hybrids of these two historically imported strains, and key selection traits in United States (US) breeding programs are productivity and resistance traits to certain pathogens (Saelao et al, 2020). In Northern Europe, the favored use of South-European honey bees has led to multiple admixture events between subspecies and the extinction of native honey bees (Bieńkowska et al, 2021;Ruttner, 1995). Furthermore, these bees are also threatened by the widespread use of stabilized hybrid strains such as Buckfast (Adam, 1983;Bieńkowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Northern Europe, the favored use of South-European honey bees has led to multiple admixture events between subspecies and the extinction of native honey bees (Bieńkowska et al, 2021;Ruttner, 1995). Furthermore, these bees are also threatened by the widespread use of stabilized hybrid strains such as Buckfast (Adam, 1983;Bieńkowska et al, 2021).…”
Section: Introductionmentioning
confidence: 99%